DIMENSI PELAYANAN PADA PERGURUAN TINGGI: STUDI PADA MAHASISWA PASCASARJANA - Khuzaini khuzaini; Maskur Maskur (At-Tadbir : jurnal ilmiah manajemen, 2019)
Customer satisfaction is a very important factor in a business field including a non-profit business. One of the factors causing customer satisfaction in service businesses is the quality of service. With the existence of service quality factors, it is expected to increase customer satisfaction. Identifying the dimensions of service quality is certainly a very important thing in an effort to satisfy customers. Therefore this study seeks to build a dimension that has been mentioned in various literatures of course with some adjustments. This research was conducted at the Higher Education organization (non-profit) which aims to serve students. The dimensions used are Tangible, Reliability, Responsiveness, Assurance and Empathy. The analytical method used is to use factor analysis using the Partial Least Square (SEM-PLS) approach. This research is a pilot study (pilot-test) involving a sample of 82 master students. The test results show that the responsiveness indicator is not able to explain the service quality dimension variables. Keywords: Service Quality, PLS, postgraduate, pilot-test, satisfaction